Modeling Gen Z students’ financial behavior: Social media and mediated intention effects - Butar Butar, Ningsi; Iramani, Rr (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
The rapid development of social media in the digital era has changed the way Generation Z accesses and processes financial information, which has the potential to influence their financial knowledge, attitudes, and behaviors. This study aims to analyze the influence of social media on financial knowledge, financial attitudes, and financial behaviors among Generation Z students in Surabaya. It also aims to examine the mediating role of intention in the relationship between financial attitudes and financial behavior. Sampling was conducted using purposive sampling, namely students who fall into the Gen Z classification and use digital technology in financial transactions. Data collection was carried out through a survey by distributing questionnaires to respondents. The results of the study indicate that social media influences financial attitudes and behavior, but does not influence financial knowledge. Financial knowledge contributes to the formation of financial attitudes, while financial attitudes influence financial behavior through intention as a mediator. The implication is that efforts to improve students' financial behavior should focus on strengthening intention and promoting the wise use of social media. Additionally, the results of this study provide theoretical implications for the development of a financial behavior model with social media as one of the antecedent variables.